Modulation of Elevated Triglycerides and Mild NAFLD using Targeted Frequency Bioelectronic Therapy: A Case Study in a Young Healthy Male (London Journal of Medical and Health Research, 2025)
Triglycerides (TG), together with total cholesterol (Chol-T) as well as high and low- density lipoproteins (HDL, LDL), are lipids of fundamental importance for determining cardiovascular risk (Henein M.Y., 2023). TG are molecules composed of a glycerol nucleus and three fatty acids, fats that we can find in both animal and vegetable foods. They represent the main form of storage and transport of fatty acids within cells and in the plasma, while it is in the liver that the fundamental steps for the metabolism of fatty acids occur (Strable M.S, 2010). Levels of TG higher than 150 mg/dl fasting are characteristic of a state of dyslipidemia (Pappan N. et al., 2024), which can result from a hereditary condition or an incorrect lifestyle; however, this is a condition that, if left untreated, can over time lead to severe cardiovascular consequences or to non-alcoholic fatty liver disease (NAFLD) (Alves- Bezerra M., 2019). Currently, to normalize triglyceride levels in patients with dyslipidemia, fibrates (Spence J. D., 2020), statins, or statins and ezetimibide (Ferri N., 2023) are administrated. In minor forms of hypertriglyceridemia (HTG), the administration of supplements based on Omega-3 (Rodriguez D., 2022) or berberine (Osadnik T., 2022), silymarin (Li S. et al., 2024) in addition to the diet (Hyun Suk Lee, 2021) and physical exercise (Petridou A., 2022) are also accompained. Bioelectronic medicine (BEM) is increasingly expanding its field of research, today particularly oriented towards the modulation of the activity of the vagus nerve and its effects, for example, on the release of inflammatory cytokines (Borovikova et al., 2000); this innovative approach is increasingly moving towards new directions to the point of involving its effects on inflammatory, cardiovascular, neurodegenerative diseases (Pavlov A. P., 2022), urological disorders (Peregrine B.O., 2017), etc..In this study, we wanted to verify the effectiveness of the BEM approach on human metabolism using a specific frequency indicated by the Grabovoj method (Grabovoj G., 2013) for the physiological regeneration of TG levels; we also wanted to verify the selectivity of the effects on the organism of the frequency used for the treatments, evaluating the variations in the levels of Chol-T, HDL, LDL and Glu at time zero and at the end of the work. From this assumption, we wanted to verify the response of a young, healthy male practising competitive sport characterized by non-physiological levels of TG (409 mg/dl) and a mild form of NAFLD by first treating him with berberine/silymarin/Omega-3 and an appropriate diet and then subjecting him to treatments with a specific frequency on the body applied via electrodes emitted by a BioLife-Regen frequency generator.
Keywords: chronic pain.; biomarkers; opioid; opioid use disorder; neural alterations; Adults; Healthcare demand; Income inequalities; Propensity Score; Health Policy.; mortality; admissions; emergency department.; attendance; brought-in-dead